Penentuan Kriteria Penerima Beasiswa Berprestasi Menggunakan Metode Analytical Hierarchy Process - Anti Nada Nafisa; Erika Nia Devina Br Purba; Nurul Adawiyah Putri; Debi Yandra Niska (LPPM Universitas Bina Sarana Informatika, 2022)
Masalah ekonomi Indonesia menjadi penghambat keberlangsungan pendidikan Indonesia, oleh karena itu dibuatlah program beasiswa. Beasiswa dirancang bagi mahasiswa berprestasi yang kurang mampu. Ketika memutuskan penerima beasiswa yang baik, pilihan dibuat bahwa siswa yang dipilih memenuhi kriteria. Penentuan kriteria terbaik untuk menentukan penerima beasiswa dapat dilakukan dengan menggunakan salah satu metode dalam sistem pendukung keputusan yaitu metode Analytical Hierarchy Process, dimana persepsi manusia menjadi input utamanya. Adapun kriteria yang dipakai dalam penelitian ini adalah nilai, prestasi akademik, dan pendapatan orang tua. Berdasarkan penelitian yang telah dilakukan, didapatkan bahwa kriteria yang sangat mempengaruhi keputusan penerima beasiswa adalah kriteria nilai yang dicapai mahasiswa dengan persentase 64,8%. Economic problems in Indonesia are an obstacle to the continuity of education in Indonesia, thus creating a scholarship program. Scholarships are intended for underprivileged students and outstanding students. To determine scholarship recipients, a selection is carried out where there are several predetermined criteria, taking into account the most influencing aspects in the selection of scholarship recipients. To get the best criteria in determining scholarship recipients, it can be done using a Decision Support System with the Analytical Hierarchy Process method where the main input is human perception. The criteria used in this study are Grades, Student Achievements, and Social Studies which are considered the most influential in the selection of outstanding scholarships. Each criterion will be given a weight, which is done by comparing the criteria with each other. The results of this study indicate that the criteria that greatly influence the determination of scholarship recipients are in terms of the value obtained by students, with a percentage of 64.8%, Student Achievement with a percentage of 22.9% and Social Studies with a percentage of 12.2%